Versatile biomimetic haze films for efficiency enhancement of photovoltaic devices. Issue 3 (3rd November 2016) - Li, Kan; Zhang, Yaokang; Zhen, Hongyu; Wang, Helin; Liu, Shenghua; Yan, Feng; Zheng, Zijian
Abstract : A low-cost biomimetic haze film (BHF) is fabricated by one-step replica molding of the petal texture of yellow roses with polydimethylsiloxane (PDMS). Abstract : A low-cost biomimetic haze film (BHF) is fabricated by one-step replica molding of the petal texture of yellow roses with polydimethylsiloxane (PDMS). The BHF possesses very high haze transmission (75%) and ultrahigh diffusion transmittance (97%), superior anti-reflection ability, remarkable enhancement of light absorption at small incidence angles, and superb resistance to strong acids. When attached on top of the glass side of photovoltaic cells, the BHF significantly elongates the photon pathway in the active layer and enhances the light harvesting of the solar devices. As a result, the power conversion efficiency of Si solar cells, organic solar cells (OSCs) and perovskite solar cells (PSCs) is respectively improved remarkably by 6.8%, 10% and 15%. In addition, >65% of the photocurrent is maintained even at an extremely small light incidence angle (10°), which equals more than 2.7 times the efficiency enhancement of the solar cell without the BHF.